Pengaruh Kinerja Keuangan, Kebijakan Dividen, dan Struktur Modal Terhadap Nilai Perusahaan Otomotif di Masa Pandemi Covid-19 - Chalimatuz Sadiyah; Tri Meidiana Ardanari (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2023)
This study aimed to analyse the relationship between financial performance variables (ROA), dividend policy, and capital structure as intermediary variables on firm value. This research was a quantitative descriptive study. The research subjects used were the automotive industry which was registered on the Indonesia Stock Exchange website in the 2019-2021 period. The sampling technique used is a purposive sampling technique based on: 1) automotive industries that reporting sustainable financial data, 2) automotive industries without loss status, and 3) automotive industry without negative assets during period. The data analysis technique used is multiple linear regression and path analysis. The results of this study indicate that the variables of financial performance, dividend policy and capital structure have no significant effect on firm value. Meanwhile, the dividend policy variable has an effect on firm value with a mediating capital structure.